Urban mobility in the digital era: An exploration of travellers' expectations of MaaS mobile-technologies. (November 2020) - Lopez-Carreiro, Iria; Monzon, Andres; Lopez, Elena; Lopez-Lambas, Maria Eugenia
Abstract: Mobility-as-a-Service (MaaS) represents a technological innovation with the potential to revolutionise the urban mobility paradigm, triggering a societal shift towards more sustainable travel behaviours. Successful implementation of these novel mobility solutions will largely rely on travellers' adoption of MaaS mobile-technologies. As with any new technology, the qualitative, user-centric research approaches focusing on the individuals' point of view may be significantly beneficial for the initial stages of development. Within this context, the paper explores which services should be offered by MaaS technologies to provide travellers with tailored mobility solutions that satisfy their daily needs. To that end, six Focus Groups were conducted in the metropolitan area of Madrid (Spain). We examined the services expected by travellers when adopting MaaS and compared them with those already identified from a comprehensive literature review. Our analysis revealed six new services that had not been recognised previously, including route optimisation and the provision of real-time information on the following five categories: passenger crowding, pollution levels, route facilities, vehicle conditions, and urban security. Overall, our results also highlighted the relevance given to the availability of information on environmental and health implications of travel behaviours. We believe that our findings provide valuable guidelines for the development of successful MaaS mobile-technologies. The incorporation of the travellers' perspective enables a more thoughtful design of these innovations and, thus, maximises their potential for addressing the limitations of our complex mobility-systems in meeting urban sustainability goals. Highlights: Understanding travellers' expectations is key for designing successful MaaS technologies. MaaS technologies should provide travellers with services that satisfy their daily needs. Six Focus Groups are conducted to explore travellers' perspective in Madrid (Spain). Travellers demand information about the environmental and health implications of their behaviours.